Cerebral edema in drug addicts - Daruši, Dragana J.; Radulović, Danka M.; Radovanović, Ivana D. (Vojnosanitetski pregled, 2014)
Background/Aim. The effect of drugs leaves permanent consequences on the brain, organic in type, followed by numerous manifestations, and it significantly affects the development of mental dysfunctions. The clinicians are often given a task to estimate a patient’s personality during treatment or during experts estimate of a drug addict. The aim of this research was to determine the differences, if any, in characteristics of addicts experience and personality traits in drug addicts with or without cerebral edema. Methods. The research was conducted on a sample of 252 male drug addicts, the average age of 23.3 (SD = 4.3) years. Cerebral edema was confirmed on magnetic resonance (MR) images of the brain performed during the treatment of the addicts. The participants were tested by the psychologists using Minnesota Multiphasic Personality Inventory (MMPI-201) test, and the data were processed using canonical discriminate analysis within the SPSS program. The dependent variable in the study was cerebral edema. A block of independent variables, designed for the requirements of this study, consisted of two subgroups. The first one consisted of 12 variables describing the relevant characteristics of drug abuse. The second subgroup consisted of 8 psychopathological tendencies in the personality defined by the mentioned test. Results. Cerebral edema was confirmed in 52 (20.63%) of the drug addicts. The differences between the groups of drug addicts with and without cerebral edema were determined in the following: the time span of taking drugs (0.301), use of alcohol parallel with drugs (0.466), and treatment for addiction (0.603). In the drug addicts with a cerebral edema, MMPI-201 confirmed the increase in the scales for hypochondria, psychopathic deviations and psychastenia, and the decrease in the scales for schizophrenia and depression. Conclusion. Our study confirmed a possible connection between cerebral edema and personality traits in a number of the examined drug addicts. Considering the fact that practice often requires personality estimation, regardless whether it is about treatment or expert’s estimate, it is necessary to further research in this direction.